2012
DOI: 10.1063/1.3678024
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-protein bioelectronic devices with wavelength-dependent photoresponse

Abstract: We implemented a nanoelectronic interface between graphene field effect transistors (FETs) and soluble proteins. This enables production of bioelectronic devices that combine functionalities of the biomolecular and inorganic components. The method serves to link polyhistidinetagged proteins to graphene FETs using the tag itself. Atomic Force Microscopy and Raman spectroscopy provide structural understanding of the bio/nano hybrid; current-gate voltage measurements are used to elucidate the electronic propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…47 The resulting MoS 2 –protein hybrid structure is shown schematically in Figure 4b,c. The histidine tag has been used as an anchor site in other biosensor systems, including those based on carbon nanotube 12 and graphene 13 FETs. These previous functionalization schemes relied upon nitrilotriacetic acid to bind Ni ions, resulting in a ~2 nm thick linker layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…47 The resulting MoS 2 –protein hybrid structure is shown schematically in Figure 4b,c. The histidine tag has been used as an anchor site in other biosensor systems, including those based on carbon nanotube 12 and graphene 13 FETs. These previous functionalization schemes relied upon nitrilotriacetic acid to bind Ni ions, resulting in a ~2 nm thick linker layer.…”
Section: Resultsmentioning
confidence: 99%
“…These previous functionalization schemes relied upon nitrilotriacetic acid to bind Ni ions, resulting in a ~2 nm thick linker layer. 13 The MoS 2 functionalization scheme presented here is a simple, one-step surface chemistry that results in an extremely short linker. This is expected to ensure strong electrostatic coupling of target binding events to the MoS 2 channel and should render the devices robust against screening that occurs for measurements in ionic liquids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy measurements showed an increase in the ratio of the intensity of the D band to the G band after diazonium salt treatment, consistent with the creation of covalent bonds to the NT sidewall (see Supplemental Figure 2 in the Supporting Information). 29 …”
Section: Resultsmentioning
confidence: 99%
“…Protein sensors. Lu et al suggested that His-tagged proteins are easily detected by graphene FET (G-FET) biosensors by the binding of Ni ions to the nitrilotriacetic acid (NTA) (Lu et al, 2012). FET based on aptamer-modified graphene easily detected the IgE protein because the reaction between IgE aptamers and IgE protein is highly active; the solution was stirred for several tens of seconds after the addition of each analyte (Ohno et al, 2010b).…”
Section: Graphene-based Fet Biosensorsmentioning
confidence: 99%